Canva for Education Project Based Learning Model for Presenting Fiction Stories - Hidayani, Elif (Jurnal Pendidikan Profesi Guru, 2024)
This research aims to increase creativity and learning outcomes in presenting fictional stories using the Canva for Education-based Project Based Learning model for class VI/b students at MIS Al Azhar Kuta. This research is a type of Classroom Action Research which was carried out in two cycles. The research subjects were class VI/b students. The data collection technique in this research uses the test method, then the data is analyzed using quantitative descriptive methods. In the pre-cycle the percentage of student learning creativity was 22%, then in the first cycle creativity gradually increased to 61% and 70%. In cycle II creativity increased to 83% and 91%. The average student learning outcome score in the pre-cycle was 22% complete and 78% incomplete, in the first cycle the average student score was 48% complete and 52% incomplete. Furthermore, in cycle II the average score of student learning outcomes reached 91% complete and 9% incomplete. So it can be concluded that the Project Based Learning model based on Canva for Education can increase the creativity and learning outcomes of class VI/b students with the material of presenting fictional stories.